Local Government Policy in the Marketing of Home Industry Products in Bumiharjo Village - Juliati Prihatini; Hasna Azmi Fadhilah; Achmad Bagas Pangestu; I Made Aldy Wijaya (Asia Pacific Journal of Management and Education (APJME), 2024)
The home industry is crucial for regional economic growth by producing quality local products, requiring local governments to support its development through effective regulations. This research aims to assess the effectiveness of government policies in marketing home industry products in Bumiharjo Village and to identify internal and external factors that impact product distribution, while evaluating regional support initiatives like the Join Marketing Center (JMC) and promotional efforts. This study employs a qualitative method with an inductive approach, utilizing both primary and secondary data sources. Data were gathered through interviews, observations, and documentation, and analyzed using data reduction, display, and verification techniques. The findings indicate that the current marketing policy for home industry products in Bumiharjo Village remains suboptimal due to the lack of official regulations. Key obstacles include unformalized marketing policies for home industry products and limited production capabilities due to inadequate equipment and capital. The Regional Government has made efforts to address these challenges by establishing the JMC, promoting products through regional exhibitions, and endorsing them on official social media channels managed by the Regent and Deputy Regent of Way Kanan. These initiatives highlight the need for formalized policies and increased support to enhance the marketing and distribution of local products.